Fertility intention of college students responding to the three-child policy in Guangzhou, China: a cross-sectional study - Wang, Xiaona; Cheang, Chonin; Zhong, Xiaoqing; Wu, Shengguang; Xia, Sujian (Frontiers in Sociology, 2025)
BackgroundIn recent decades, a noticeable decline in birth rates has been observed globally, particularly in developing countries. Aganist this backdrop, this study investigates fertility intentions and associated factors among college students in Guangzhou, China, within the context of China’s relaxation of the three-child policy in May 2021.MethodsBetween May and July 2021, a cross-sectional survey involving 971 participants was conducted. Participants provided information regarding their demographic characteristics, childbearing preferences, and the factors influencing their fertility plans.ResultsFrom the data collected, only 43.9% of the participants planned to have children in the future, while 29.8% were unsure, and 26.3% had no intention of having children. It was observed that fertility knowledge among college students in Guangzhou was somewhat limited. Certain factors, like a harmonious family atmosphere, absence of gender preference, and positive peer influences, correlated with higher fertility intentions. However, those who did not perceive fertility as an essential life experience exhibited lower fertility intentions.ConclusionOur findings primarily indicate that college students in Guangzhou possess limited fertility knowledge. Although the new fertility policy might be beneficial, there is no guaranteed assurance that it will lead to a rise in fertility rates among this demographic.